Effect of Team Game Tournament (TGT) Learning Model on Science Learning Outcomes of Fourth Grade Students - Sitohang, Mei Evelina; Simarmata, Radode K.; Thesalonika, Emelda (CV Putra Publisher, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model on the social studies learning outcomes of fourth-grade students at the UPTD of Public Elementary School 124392 Pematangsiantar. This study employed a quantitative pre-experimental design with a One Group Pretest-Posttest Design. The sample size was 25 students. Data collection techniques used included pretest-posttest and documentation. Data were analyzed using the Shapiro-Wilk normality test and the t-test. The results showed that the average pretest score was 52.96, with a 12% completion rate, which then increased to 82.32, with a 100% completion rate on the posttest. The results of the normality analysis show that the pretest data has a significant value of 0.088>0.05 and the posttest value has a significant value of 0.289>0.05, so the results of the normality analysis have normally distributed data.Based on the results of the hypothesis test, the calculated t value was 12.641 and the t value was 2.064, with a significance level of 0.05. Since the probability of significance is 0.000 <0.05, or the calculated t value > t table, and the results obtained (t count = 12.641 > t table = 2.064), Ho is rejected and Ha is accepted. Therefore, it can be concluded that the Teams Games Tournament (TGT) learning model has an effect on the social studies learning outcomes of fourth-grade students at the UPTD of SD Negeri 124392 Pematangsiantar